Innovation and challenges of CSCC finance - Song, Hua, 1969-; Chen, Sijie (London : Renmin University, 2019)
This is a case study of CSCC Financial Information Services Co., Ltd. CSCC is an Internet financial company based on financial development of the supply chain. It is a key "Internet +" and national "mass entrepreneurship and innovation" platform supported by the State-owned Assets Supervision and Administration Commission of the State Council. It is designed to provide free supply-chain management services for large enterprises based on Internet thinking. It can utilize big enterprises' good credit resources and help the industry chain to clear enterprises' triangle debt and help the big enterprises to reduce costs and increase efficiency. On the other hand, it can help solve the financing difficulties and high expenditure of small and medium-sized enterprises, in order to impel the benign development of the industrial chain and realize a multi-win-win situation. However, with the call of national policies and the development of the supply-chain finance market, many financial companies are ready to enter the supply-chain finance market. Therefore, how to deal with the relationship with financial companies has become a difficult problem facing CSCC. In addition, as more and more enterprises begin to imitate the business model of CSCC, how to adjust its own profit model and how to improve the "credit" ability of the platform have become challenges that the future development of CSCC needs to face.
Originally Published InSong, H., & Chen, S. (2019). Innovation and Challenges of CSCC Finance. Beijing, China: Renmin University Business School.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Financial services industry -- Technological innovations; Business planning